To neither bleed nor clot: That is the question. Issue 3 (13th September 2016) - Davies, Rhian E.; Gilchrist, Ian C.
Key Points: Patients with atrial fibrillation (AF) when stented with thin‐strut colbalt chrome stents may have a similar outcome to patients without AF. Management of patients with AF potentially place patients at enhanced bleeding risk with triple antithrombotic therapy, or potential thrombotic risk if either oral anticoagulation is held or anti‐platelet therapy is truncated. Guideline‐based oral anticoagulation for AF is expanding this patient group presenting to the cardiac catheterization laboratory, yet management decisions are still based on limited studies and rely on expert concensus.